20-Degree Elevation to Reduce Swelling and Pain After Lower Extremity Open Reduction and Internal Fixation Surgery - Eni Purwanty; Riri Maria; Masfuri Masfuri (Jurnal Keperawatan Indonesia, 2021)
Surgery for open reduction and internal fixation (ORIF) causes tissue swelling and pain in the surgical area. Swelling and pain can be reduced by performing distal elevation in the area of surgical ORIF. This study aimed to determine the effect of a 20° elevation on swelling and pain level of patients after surgery for ORIF of the lower extremities. A quasi-experimental design with one intervention group (pretest and posttest) and one control group was implemented. Thirty-four post-operative ORIF patients treated in one hospital in South Sumatera met the inclusion criteria and were divided into intervention and control groups. Swelling circumference was measured using tape meters, and pain level was assessed with a numeric rating scale. Dependent t-test, independent t-test, and Pearson correlation were applied for data analysis. Results showed that the average difference in swelling circumference and pain level between pre and post intervention was 1.93 ± 0.25 and 1.29 ± 0.35, respectively. Significant differences were found in the mean swelling circumference and pain level between the intervention and control groups (p = 0.000). Therefore a 20° elevation of lower extremity on the second day after ORIF for two days can be an alternative for nursing intervention to reduce swelling and pain. Abstrak Elevasi 20 Derajat untuk Menurunkan Pembengkakan dan Nyeri Pasca Bedah Open Reduction and Internal Fixation Ekstremitas Bawah. Pembedahan open reduction and internal fixation (ORIF) menyebabkan pembengkakan jaringan dan nyeri pada area pembedahan. Pembengkakan dan nyeri dapat dikurangi dengan melakukan elevasi distal pada area bedah ORIF. Penelitian ini bertujuan untuk mengetahui pengaruh elevasi 20° terhadap tingkat pembengkakan dan nyeri pada pasien pasca operasi ORIF ekstremitas bawah. Desain kuasi-eksperimental dengan satu kelompok intervensi (pretest dan posttest) dan satu kelompok kontrol diterapkan pada penelitian ini. Tiga puluh empat pasien ORIF pasca operasi yang dirawat di salah satu rumah sakit di Sumatera Selatan memenuhi kriteria inklusi dan dibagi menjadi kelompok intervensi dan kontrol. Lingkar pembengkakan diukur menggunakan meteran pita, dan tingkat nyeri dinilai dengan skala numerik. Dependent t-test, independent t-test, dan korelasi Pearson digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa rerata perbedaan lingkar bengkak dan tingkat nyeri antara sebelum dan sesudah intervensi masing-masing adalah 1,93 ± 0,25 dan 1,29 ± 0,35. Perbedaan bermakna ditemukan pada rerata lingkar pembengkakan dan tingkat nyeri antara kelompok intervensi dan kelompok kontrol (p = 0,000). Oleh karena itu, elevasi 20° ekstremitas bawah pada hari kedua setelah ORIF selama dua hari dapat menjadi alternatif intervensi keperawatan untuk mengurangi pembengkakan dan nyeri. Kata Kunci: bengkak, ekstremitas bawah, elevasi, nyeri, open reduction and internal fixation